Disordered Eating Attitudes and Exercise Behavior among Female Emirati College Students in the United Arab Emirates: A Cross- Sectional Study - Al Sabbah, Haleama; Muhsineh, Shatha (Arab Journal of Nutrition and Exercise (AJNE), 2017)
Background: Growing evidence is showing high levels of physical inactivity and disordered eating attitudes among young females in the United Arab Emirates. This is clearly concerning, but little is known about the activity level of those with disordered eating attitudes and their dieting behavior. This study examines the female Emirati college students’ disordered eating attitudes and its relation to exercise behavior. Method: A cross- sectional study using a validated and reliable questionnaire was conducted on 242 Emirati female students attending a public university in Dubai. Eating Attitudes Test- 26 (EAT26) was used to measure eating attitudes and the short International Physical Activity Questionnaire (IPAQ) was included to measure physical activity level. A systematic random sampling from a list of classes in the fall 2014 semester was used for recruitment. The university’s Research Ethics Committee approved the study and consents were obtained from participants. SPSS v.21 was used for data analysis. Chi-square test was used to compare frequencies. Significance level was set at 0.05. Results: The participants’ mean age and standard deviation (Mean± SD) was 19 ±1.3 years. 31.4% of the participants showed disordered eating attitudes. The percentage of participants engaged in at least one concerning behavior in the past six months was 43.8%. A membership in a health club was significantly related to disordered eating attitudes (p <0.01). A high level of physical activity was correlated with laxative use, over the counter supplements, and exercising for more than 60 minutes to control weight (p<0.05). Conclusion: There is a great need for intervention programs and policies to contain the level of abnormal eating attitudes and promote healthy level of physical activity among college students.